Respuesta :

Answer:

x = 6[tex]\sqrt{2}[/tex]

Step-by-step explanation:

Note the triangle is a right- isosceles, with equal legs = 6

Using Pythagoras' identity on the right triangle.

x² = 6² + 6² = 36 + 36 = 72 ( take the square root of both sides )

x = [tex]\sqrt{72}[/tex] = [tex]\sqrt{36(2)}[/tex] = [tex]\sqrt{36}[/tex] × [tex]\sqrt{2}[/tex] = 6[tex]\sqrt{2}[/tex]

Answer:

6[tex]\sqrt{2}[/tex]

Step-by-step explanation:

We should be using pythagoras theorem

6^2 + 6^2 = 72

[tex]\sqrt{72}[/tex] is the length of x

it is also equal to [tex]\sqrt{36*2}[/tex]

The square root of 36 is 6

and the square root of 2 is [tex]\sqrt{2}[/tex]

Thus the ans is 6[tex]\sqrt{2}[/tex]